Pendampingan Strategi Branding dan Pembuatan Laporan Keuangan bagi Wirusaha Pemula Milenial - Dwi Hasmidyani; Ikbal Barlian; Siti Fatimah; Edutivia Mardetini; Dian Eka Amrina (IKIP PGRI Bojonegoro, 2023)
The purpose of this community service activity is to provide assistance in branding strategies (labeling and packaging) and making financial reports, as well as providing label and packaging assistance for millennial beginner entrepreneurs. This is important to do as part of increasing income and orderly administration of financial reporting for millennial entrepreneurs. The number of participants involved in mentoring in this community service activity is 10 beginner entrepreneurs belonging to the millennial generation. In delivering this mentoring material, several methods were used, including the tutorial method, and the field trip method. After being given the mentoring material, there was an increase in the target audience's understanding of the importance of labeling and packaging, as well as the preparation of financial reports.Tujuan kegiatan pengabdian kepada masyarakat ini adalah untuk melakukan pendampingan strategi branding (labeling dan packaging) dan pembuatan laporan keuangan, serta pemberian bantuan label dan kemasan bagi wirausaha pemula milenial. Hal ini penting dilakukan sebagai bagian dari meningkatkan pendapatan dan tertib administrasi pelaporan keuangan wirausaha pemula milenial. Jumlah peserta yang terlibat dalam pendampingan pada kegiatan pengabdian kepada masyarakat ini adalah 10 orang wirausaha pemula yang tergolong generasi milenial. Dalam penyampaian materi pendampingan ini, digunakan beberapa metode antara lain metode tutorial, dan metode field trip. Setelah diberikan materi pendampingan, terdapat peningkatan pemahaman khalayak sasaran terhadap pentingnya labeling dan packaging, serta pembuatan laporan keuangan.